2011
DOI: 10.1063/1.3641974
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ultraviolet photon irradiation on the transition metal impurities in LaAlO3

Abstract: By measuring electron spin resonance (ESR) spectra at the X-band frequency and absorption spectra from the visible to ultraviolet region at room temperature, it was confirmed that perovskite single crystal LaAlO3 contains Cr and Fe as impurities. When LaAlO3 is exposed to photons with energies higher than 4.5 eV, the intensities of ESR signals due to Cr3+ and Fe3+ decrease, which indicates that electrons released by the photon irradiation are captured by Cr3+ and Fe3+. Concurrently with this, a broad optical a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 37 publications
2
18
0
Order By: Relevance
“…We rule out a role of any magnetic impurity element such as Cr 3+ and Fe 3+ in the Al-based compounds1417), especially in LSAT and LSAO and possibly in LaAlO 3 as well. PIXE measurements showed that no impurities could be detected within the resolution limit (~10 ppm) in LaAlO 3 (see Figure S12) and any of these substrates except SrTiO 3 (~7 ppm of Cr and ~160 ppm of Fe; not shown in Figure).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We rule out a role of any magnetic impurity element such as Cr 3+ and Fe 3+ in the Al-based compounds1417), especially in LSAT and LSAO and possibly in LaAlO 3 as well. PIXE measurements showed that no impurities could be detected within the resolution limit (~10 ppm) in LaAlO 3 (see Figure S12) and any of these substrates except SrTiO 3 (~7 ppm of Cr and ~160 ppm of Fe; not shown in Figure).…”
Section: Discussionmentioning
confidence: 99%
“…This material is a promising gate insulator for advanced Metal-Oxide-Semiconductor (MOS) devices101112. However, it has been reported to possess localized mid-gap states due to various types of defects — interstitials, vacancies, anti-sites, impurities — causing leakage current and it is important to understand the various defects and their dynamics both experimentally and theoretically13141516171819. On the other hand, lattice strain plays an important role on the defects and their dynamics and hence on the related physical properties20.…”
mentioning
confidence: 99%
“…Electron spin resonance (ESR) studies can allow measurements of the V + O defect in LAO. Indeed ESR studies of LAO [30,31] have attributed certain signals in their measured spectra to this defect. In order to confirm the prediction that these signals are due to the V + O defect the g-tensor and hyperfine values of the defect can be calculated and compared to Singh et al [31].…”
Section: The G-tensor and Hyperfine Splittings Of V + Omentioning
confidence: 99%
“…Experimentally, defects in LAO have been probed using photoluminescence (PL) spectroscopy [28,29] and electron spin resonance (ESR) [30,31]. Kawabe et al [28] excited LAO using a 266 nm pulsed laser and observed slow emission at 2.5 eV (490 nm), which they attributed to oxygen vacancies, due to its sensitivity to the oxygen content.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation